About ogling: the set table in “My Porto”, by Mário Claudio - Costa, Mariana Caser da (2014)
Mario Claudio’s bibliographic production, which spans varied genders, remarkably plays with literature’s ability of representing. In Meu Porto (My Porto), work published in 2001, the Portuguese writer fosters a walk around the burgh through an intersemiotic trip which invites different artistic languages and ways of expression to the text, in a richly illustrated edition, with images based on the city he was born, that intends to reveal, through the biases of Porto’s landscape, art, mysticism, cultural and culinary tripeira tradition, a kind of a city report. What is interesting about the defended ideas in this article is how the author recreates his Porto by the pathway of the food, of the Portuguese rich table, by matching it with important people who had been in town. Therefore, literature can be read by a subjective speech which, highlighting traditional aspects of Portuguese culture, especially food, reveals, in this dialog between the letters and the culinary art, images, flavors, and palatable stories to the taste of the text.